Homem, chefe de família, dilacerado em O casamento, de Nelson Rodrigues - Capelozi, Lays da Cruz (2016)
This work presents a reflection on the novel by Nelson Rodrigues O Casamento, published originally in 1966. We will see an analysis on the wedding theme in the work of Nelson Rodrigues in a more comprehensive way. Then, we worked through the novel, highlighting the characters and their plots and presented the family structure. Finally, we will analyze how are worked the father figures of the novel. All discussions permeate through dialogue with Sigmund Freud.